GAYA BERBELANJA DI MASA DEPAN PADA ERA INDUSTI 4.0 DALAM MENGHADAPI KEGAGALAN PASAR - Wati, Titi Rahma; Aisyah, Nur (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose-This research aims to analyze the effect of servicescapes and experiences on future shopping experiences in industrial era 4.0 as an effort to avoid market failure. Design/methodology/approach- Research method with quantitative approach. The research sample consisted of 100 traders at the Islamic Market Center Saporete Brebes obtained using Proportionate Stratified Random Sampling. Findings-The results showed that there is a positive and significant effect of servicescapes on efforts to avoid market failure through income redistribution; experienscapes has a positive but insignificant effect on efforts to avoid market failure through income redistribution. Implication-The local government is required to make policies related to market implementation which are closely related to economic aspects by focusing on the orientation and shopping style of consumers in the industrial era 4.0. Future shopping styles in the industrial revolution 4.0 era must be able to combine online shop and physical shop styles. both are complementary not substitute. Keywords:Experienscapes; Servicescapes; Shopping experience; Saporete Brebes Sunday Market